Investigation of glass-ceramic lithium thiophosphate solid electrolytes using NMR and neutron scattering. (November 2021) - Self, Ethan C.; Chien, Po-Hsiu; O'Donnell, Lauren F.; Morales, Daniel; Liu, Jue; Brahmbhatt, Teerth; Greenbaum, Steven; Nanda, Jagjit
Abstract: Solid-state Li batteries require solid electrolytes which have high Li + conductivity and good chemical/mechanical compatibility with Li metal anodes and high energy cathodes. Structure/function correlations which relate local bonding to macroscopic properties are needed to guide development of new solid electrolyte materials. This study combines diffraction measurements with solid-state nuclear magnetic resonance spectroscopy (ssNMR) and neutron pair distribution function (nPDF) analysis to probe the short-range vs. long-range structure of glass-ceramic Li3 PS4 -based solid electrolytes. This work demonstrates how different synthesis conditions (e.g., solvent selection and thermal processing) affect the resulting polyanionic network. More specifically, structures with high P coordination numbers (e.g., PS4 3− and P2 S7 4− ) correlate with higher Li + mobility compared to other polyanions (e.g., (PS3 )n n– chains and P2 S6 4− ). Overall, this work demonstrates how ssNMR and nPDF can be used to draw key structure/function correlations for solid-state superionic conductors. Graphical abstract: Image 1 Highlights: NMR and nPDF are used to probe the local structure of Li3 PS4 -based solid electrolytes. The effects of different compositions and thermal treatments on structure and Li +  conductivity are reported. Polyanions with greater P-S coordination (e.g., PS4 3− and P2 S7 4− ) correlate with higher Li + mobility.